Edu-Tourism: Leisure Motivation, Travel Behaviour and Travel Satisfaction among Foreign Students in Malaysia - Lee, Choon Kin (2021)
Malaysia’s aspiration to be an international education hub has over the years attracted about 100,000 foreign students annually into institutions of higher learning, generating education revenues to the national economy. Moreover, travel and tourism activities among these foreign students add to the tourism revenues and also improve the attractiveness of Malaysia’s education industry. To attract more foreign students and improve inbound tourism among them, this study assesses their leisure motivation, as leisure activities in whatever form is a basic need for well-being. This study evaluates how leisure motivation can influence their travel behaviour, and whether travel satisfaction would mediate it. Methodology used is quantitative research, with multi-stage cluster sampling and self-administered questionnaires for data collection. The sample size was 429. Hypotheses were tested using simple linear regression, multiple regression and canonical correlation analysis, to identify relationships among the three main variables leisure motivation, travel behaviour and travel satisfaction, and their sub-variables. Findings showed that leisure motivation significantly influences travel behaviour, and travel satisfaction has mediating influence on those relationships. Stimulus-avoidance factor is the strongest leisure motivator among foreign students, which significantly influences urban and adventure tourism. Intellectual factor, the second strongest, significantly influences urban and rural tourism. The third, competence-mastery factor, significantly influences sports, adventure and urban tourism. Lastly, social factor significantly influences rural tourism. Social factor has no significant influence on travel satisfaction. Adventure tourism has no significant influence on travel satisfaction.